Prospects And Challenges Of Plastic Industries In Bangladesh - Islam, M Serajul (Journal of Chemical Engineering, 2012)
Plastic is an engineered material used to manufacture a wide variety of products to meet the domestic demand in Bangladesh as well as some products are exported. The plastic industry has emerged as an important industrial sector in the country during the last two decades. At present there are 3000 plastic manufacturing units, 98% of which belong to the Small-Medium Enterprises (SMEs). Domestic market size is Tk 7,000 crore. Per capita consumption of plastics in Bangladesh is 5 kg per year. The plastic sector constitutes 1.0 of GDP and provides employment for half a million people. Total export earning for both direct and deem (RMG accessories) exports is about US 337 million. An in-depth study of the plastic sector reveals multi-dimensional constraints and an excellent prospect for future growth. Major constraint in the plastic sector is the lack of an institutional arrangement dedicated to this sector, in order to provide supporting services such as skilled manpower, testing facilities for quality control, innovative technology and consultancy services. The availability of cheap labor and the fast developing plastic wastes recycling industry due to rising cost of petroleum (raw material of polymers) provide Bangladesh potential advantage of competitiveness in the global market. An expert (BUET, BCSIR, BITAC, BPGMEA) consultation meeting held on the plastic sector organized by the SME Foundation in 2008, has recommended setting up Bangladesh Institute of Plastic Engineering and Technology (BIPET). Aims and activities of this institute are given in this paper. This proposal is in the light of Indian experience. The entrepreneurs in the plastic sector have developed the plastic industries with their own initiative and finance. Now, considering huge potential of this sector and the multi-dimensional nature of the constraints, the government must provide supportive policy and institutional arrangements. DOI: http://dx.doi.org/10.3329/jce.v26i1.10176 JCE 2011; 26(1): 16-21